عمل الأطفال في ظل المعايير الدولية والتشريع الجزائري - فارق لبنى; ديدي رحمة (My University, 2017)
Summary: In view of the importance of children, international legislation is concerned with the phenomenon of child labour. International and Arab organizations have promulgated a number of conventions addressing various issues of child labour, which aim at their total elimination. s health, including, but not limited to, such charters, In 1991, the Convention on the Rights of the Child paid great attention to children's rights and to the establishment of child protection in all areas, and it had been greatly welcomed by most States. With regard to Algerian legislation, it is also concerned with child labour by establishing a legal system aimed primarily at the protection of children. The latter is an integral part of our society. In the Labour Code, the legislature provides for the legal age for admission to employment, which it sets at 16 years of age. A year of their age in employment where this prohibition came at all without any exception as to the type, circumstances or purpose of the work. ............................. الملخص : نستنتج مما سبق انه نظرا لأهمية الطفل البالغة إهتمت التشريعات الدولية بظاهرة عمل الأطفال حيث اصدرت المنظمات الدولية والعربية العديد من الإتفاقيات تعالج فيها شؤون عمل الأطفال المختلفة والتي تهدف إلى القضاء الكامل عليها، لقد قامت بتحديد جملة من الأعمال التي يؤديها الطفل و تنجم عنها اضرار تحدق بصحته ومن بين هذه المواثيق وعلى سبيل المثال لا على سبيل الحصر، اتفاقية حقوق الطفل سنة 1991 فأولت اهتماما بالغا بحقوق الطفل و إقرار حماية خاصة به في كافة المجالات، كما انها لقيت ترحيبا كبيرا من معظم دول. و فيما يخص التشريع الجزائري اهتم أيضا بعمل الأطفال من خلال وضعه لمنظومة قانونية تهدف بالدرجة الأولى إلى حماية الطفل، باعتبار هذا الأخير جزء لا يتجزأ من مجتمعنا حيث نص المشرع في قانون العمل على السن القانوني للإلتحاق بالعمل والذي حدده بستة عشرة سنة 16 كما حظر المشرع الأحداث الذين لم يستوف سن ستة عشرة سنة من عمرهم من العمل حيث جاء هذا المنع مطلقا ودون أن يتضمن أي استثناء من حيث نوع الشغل او ظروفه أو الغرض منه. .............................. Résumé : Compte tenu de l’importance des enfants, la législation internationale s’intéresse au phénomène du travail des enfants. Les organisations internationales et arabes ont promulgué un certain nombre de conventions traitant de diverses questions relatives au travail des enfants, qui visent à leur élimination totale. La santé, y compris, mais sans s’y limiter, de telles chartes, En 1991, la Convention sur les droits de l’enfant accordait une grande attention aux droits des enfants et à l’établissement d’une protection de l’enfance dans tous les domaines, et elle avait été très bien accueillie par la plupart des États. En ce qui concerne la législation algérienne, elle s’occupe également du travail des enfants en instaurant un système juridique visant principalement à la protection de l’enfance. Ce dernier fait partie intégrante de notre société. Dans le code du travail, le législateur fixe l’âge légal d’admission à l’emploi à 16 ans. Un an de leur âge d’emploi lorsque cette interdiction s’applique sans exception du type, des circonstances ou de l’objet du travail.